(untitled) (Global Journal of Science Frontier Research, 2020)
Assessing new maize cultivars requires studying both yield and stability performance across the major range of environments. Four trials were conducted in Sudan (Africa) during 2013 -2014. Nine maize genotypes were investigated for forage yield stability across 8 test-environments created by a combination of 2 levels of location, season and watering regime assumed to impose respective effects of salt, heat and water stresses. Wricke’s ecovalence, Eberhart-Russell and AMMI stability models were employed to study yield stability. The genotypes and watering regimes were arranged in RCB design in split-plot experiment. The study revealed maize hybrids having broad and specific responses to the studied environments with most genotypes showing consistent stability performance in the three models. Two of the 3 top-yielding hybrids showed relative stability whereas the third one exhibited specific adaptability to low yielding environments. It was concluded that yield stability could be better investigated if the varieties are purposely subjected to major factors affecting yield in a given domain. Different stability models were recommended to avoid limitations arising from using a single model.